Methods of test for boric acid, boric oxide, diRsodium tetraborates, sodium perborates and crude sodium borates for industrial use. Determination of sodium oxide and boric oxide contents and loss on ignition of 7Idi7Rsodium tetraborates Part 3, (28th February 1979) - British Standards Institution,
No abstract available